Use of Instructional Evidence Tools by the Public Prosecutor in the Criminal Prosecution Process - Harahap, Asliani (International Journal Reglement & Society (IJRS), 2020)
Instructional evidence is used to increase the judge's conviction that the defendant is guilty or not. Guidance is obtained from witness testimony, letters as well as from statements of the defendant which are put together, then put together and will produce one clue that can strengthen the judge's conviction that the defendant is guilty or not. This writing uses a normative juridical legal research method (normative research) with descriptive analytical research specifications using secondary data. The data collection procedures are in the form of documentation of notes or quotations, search of legal literature, books and others related to problem identification both offline. and online, which is then analyzed through the content analysis method (centent analysis method) with a focus on the problem of how to organize the evidence in the prosecution of a criminal case by the public prosecutor and how the prosecutor's use of instructional evidence in prosecuting criminal cases. Based on the results of the research that the provisions in Article 188 paragraph (1) of the Criminal Procedure Code state that an indication is an act, event or situation which due to its compatibility, either between one another, or with the criminal act itself, indicates that a criminal act has occurred and who the culprit. What is meant by directives is actions, events or things which are compatible with each other and the act that the accused is accused of showing clearly that a crime has been committed and who committed it.